Geochemical Analysis of Hot Springs in Massepe, Tellu Limpoe Sidenreng Rappang Regency, South Sulawesi Province, Indonesia - Arifin, M. Fauzi; Fachri, Hendra; Azikin , Busthan (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
Location of the study is administratively located in the District Tellu Limpoe, Sidenreng Rappang Regency in South Sulawesi Province. Geographically located at coordinate 119°47'00" – 119°49'00" east longitude and 04°00'00"– 04°02’00" latitude. This study aims to determine the geological conditions and geochemical, it is hot spring types, and subsurface temperature of the geothermal Massepe area Sidenreng Rappang district of South Sulawesi Province. Methods of research are conducted in the form of data collection methods and methods of geological and geochemical laboratory analysis. The geomorphology of the study area consists of one unit, the unit is flat. The type of developing river is the river periodically with stadia geomorphology including adults. The stratigraphy of the study area is divided into two units of rocks, it is rock units of ignimbrite from Pare – Pare Volcanics Formation of Pliocene age and rock units of basalt from Soppeng Volcanics Formation of Early Miocene – Middle Miocene. The structure that developed in the research area is a joint and strike–slip fault, it is a Massepestrike–slip fault. Geothermal manifestations in the study area consist of 3 stations hotspring. The percentage values of ion content of HCO3-, Cl-, and SO42- in hot water samples were analyzed, indicating that the hot springs area of research, including the chloride water type. Estimation of subsurface temperature by using the geothermometer Na - K in the research area at station 1 – 3 is 162°C - 168°C, using the geothermometer Na - K - Mg are known, that the hot springs in the area of research included in partially equilibrated.